Palestine: un féminisme de libération - Elia, Nada; Hammar, Liza; Dupuis-Déri, Francis (Micro r-m, 2024)
"Comment expliquer qu’Israël, malgré ses attaques meurtrières à Gaza et sa violation du droit international, reste à l’abri de toute véritable critique? Pourquoi de nombreuses féministes du Nord global, si promptes à dénoncer l’impact du «fondamentalisme islamique» sur les femmes palestiniennes, restent-elles silencieuses quand il s’agit de décrier l’occupation et le génocide que perpétue l’État israélien en Palestine? En déconstruisant les associations fallacieuses entre antisionisme et antisémitisme, la professeure et militante palestinienne Nada Elia, qui vit aujourd’hui aux États-Unis, rappelle la place des femmes et des personnes queers dans la lutte pour la libération de la Palestine, et revendique le démantèlement des structures coloniales qui écrasent la population à Gaza et en Cisjordanie."-- Site de l'éditeur.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; antisionisme; antisémitisme; approches et analyses; asie; cours; discipline; disicpline; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; militance; palestine; pol4212; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Une nouvelle subjectivité féminine en Iran - Khosrokhavar, Farhad (Esprit, 2023)
Les jeunes générations, notamment de femmes, rejettent un régime théocratique macabre au nom de la joie de vivre et de la liberté.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; résistance; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Invisible work at work and the reproduction of gendered social service organizations - Lavee, Einat; Kaplan, Amit (Gender, Work and Organization, 2022)
Des études démontrent que la convergence du néolibéralisme et des impératifs de la nouvelle gestion publique crée des conditions dans lesquelles les prestataires de services sociaux entreprennent divers types de travail non rémunéré, réaffirmant le rôle du genre dans la prestation de services. En s’appuyant sur ces arguments, cette étude explore le processus par lequel les pratiques non rémunérées restructurent le genre dans les organisations de services sociaux, en utilisant le concept de « travail invisible ». En appliquant la méthode d’enquête de l’ethnographie institutionnelle, nous examinons les expériences des travailleurs des services sociaux dans le secteur public israélien et opérationnalisons le travail non rémunéré comme des ressources personnelles informelles que les travailleurs fournissent aux clients. L’analyse de 185 entretiens approfondis a révélé trois principaux cadres discursifs que les travailleurs utilisent pour justifier la fourniture de ressources personnelles. Grâce à ces cadres, les pratiques informelles deviennent invisibles en tant que travail à plusieurs niveaux – pour soi-même, pour l’organisation et pour la société. Tout comme le travail invisible dans le ménage, son invisibilité sur le lieu de travail constitue une force principale dans la reproduction des organisations de services sociaux sexuées.
Keywords: approches et analyses; asie; discipline; inégalités; israël; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible; travail social; éthnographie institutionnelle

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

‘Passionate aesthetics’: T-P gender practices and discourses, and the hierarchies within lesbian (lala) communities in contemporary mainland China - Wang, Yiran (Journal of Gender Studies, 2021)
En tant que couple masculin-féminin comparable aux genres lesbiens butch-femme dans les sociétés euro-américaines, les rôles de genre TP constituent des éléments vivants dans la sous-culture lesbienne, ou lala , de la Chine continentale contemporaine. Sur la base d'une étude ethnographique menée au milieu des années 2010 à Shanghai et dans la province du Yunnan, en Chine, et en appliquant le cadre théorique de « l'esthétique passionnée », j'étudie dans cet article les discours et les pratiques pertinents pour les genres TP . J’analyse comment les hiérarchies ont été (re)produites au sein des communautés lala et comment, dans ces processus, les compréhensions (hétéro)normatives du genre et de la sexualité sont devenues à la fois sources de connaissances et objets de critique. Je soutiens que des esthétiques passionnées multiples et concurrentes, y compris la forme dominante d'hétéronormativité en Chine et les connaissances mondialisées, voire occidentales, sur le genre et la sexualité, ont entraîné trois grands types de hiérarchie parmi les lalas : des hiérarchies entre les catégories TP , qui sont paradoxalement définies par la notion de « pureté » ; les hiérarchies dans les discours féministes et activistes LGBTQ, qui banalisent, voire font taire, les incarnations quotidiennes du TP ; et les hiérarchies entre masculinité et féminité, qui encouragent diverses pratiques de masculinité féminine tout en valorisant la masculinité plutôt que la féminité.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; asie; chine; discipline; genre; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

N'est pas mère qui veut. Le paradoxe de l'adoption internationale - Reysoo, Fenneke; Bos, Pien (Nouvelles Questions Féministes, 2011)
La circulation d’enfants entre une mère biologique et des parents adoptifs soulève des questions sur la pluralité des systèmes de genre et les inégalités sociales méconnues jusqu’ici. Nous menons une réflexion sur la situation paradoxale qui lie deux systèmes de genre : en Inde, il enjoint des femmes non mariées à renoncer à vivre leur maternité et, en Occident, il pousse les femmes avec un emploi à retarder la conception de leur premier enfant, ce qui augmente le risque de fécondabilité réduite et ouvre la voie au recours à l’adoption. Notre étude, au Tamil Nadu (Inde), parmi les mères biologiques montre que la production d’enfants adoptables relève de rapports de pouvoir très complexes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; corps; cours; discipline; inde; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Doing fieldwork on women in theocratic Islamic states: A critique of the politics of empiricism - Mojab, Shahrzad (Resources for Feminist Research, 2001)
This paper examines the way some feminist advocates of cultural relativism adopt positivism and empiricism in order to discredit the radical critique of Islamization of gender relations in Iran. It argues that relativists use the positivist/empiricist cult of experience and objectivity in order to undermine the critique of policies and practices that oppress the women of Iran. The choice of a method of inquiry is not based on methodological considerations only. The researcher's political preferences, implicit or explicit, plays a significant role in the entire research process, especially in the study of sensitive issues. Although one may identify a methodological tradition with a certain brand of politics, the paper argues that methodological paradigms enter into changing relationships with structures of power.
Keywords: approches et analyses; asie; cours; discipline; discours dominant; fem1000; iran; méthodologie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; épistémologie

Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis